Trophoblast cellular adhesion molecule expression regulated by different genes and their correlation with pregnancy-induced hypertension: Trophoblast cellular adhesion molecule expression regulated - Chen, Yunshan; Fan, Yue; Pan, Xiuyu; Liao, Yunsheng; Xiang, Guochun (Cellular and Molecular Biology, 2023)
It was to study trophoblast cell (TC) adhesion molecules regulated by different genes in the placental tissue (PT) of patients with pregnancy-induced hypertension (PIH), and the correlation with the severity of PIH. 42 patients with PIH (13 cases in the mild PIH group, 11 cases in the moderate PIH group, and 18 cases in the severe PIH group) and 40 patients with normal pregnancy (NP group) were included. mRNA and protein levels in matrix metalloproteinase (MMP)-9, MMP-2, tissue inhibitor of metalloproteinases (TIMP)-1, and TIMP-2 of all patients were determined by semi-quantitative polymerase chain reaction (PCR) and Western blotting (WB), respectively. Compared to the NP group, MMP-9 and MMP-2 mRNA levels as well as their proteins in PT significantly decreased in PIH groups (P<0.05). MMP-9 mRNA was greatly lower in the severe PIH group than mild PIH group (P<0.05). MMP-2 mRNA in moderate and severe PIH groups was much lower than NP and mild PIH groups, and that in the severe PIH group was considerably lower than the moderate PIH group (P<0.05). TIMP-1 mRNA and its protein highly increased in PT in PIH groups than NP group (P<0.05). TIMP-2 mRNA was remarkably higher in the severe PIH group than in the NP group (P<0.05). mRNA and proteins of MMP-9 and MMP-2 decreased in PT of PIH patients, while TIMP-1 mRNA and its protein increased, which were correlated with the severity of PIH. MMP-9, MMP-2, and TIMP-1 were involved in the pathogenesis of PIH by regulating the infiltration of TCs.